Indonesian Nursing Students’ Perceptions of Caring in Clinical Setting: A Descriptive Qualitative Study - Herdina Mariyanti PhD; Kee Jiar Yeo PhD; Sirikanok Klankhajhon PhD; Hidayat Arifin MSN (SAGE Open Nursing)
Background Clinical education is crucial in nursing programs for preparing students to deliver compassionate, high-quality care. However, research on nursing students’ perceptions and expressions of caring behaviors in clinical settings is limited, particularly in Indonesia. This study aims to explore Indonesian nursing students’ views on caring behaviors in clinical settings, addressing a significant gap in nursing education research within the Indonesian context. Methods A descriptive phenomenology research design was employed in this study. Nursing students’ views and perceptions of caring were obtained through telephone interviews with semistructured questions. The research participants comprised 20 undergraduate nursing students undergoing clinical education at nursing education institutions in Surabaya, Indonesia, obtained through purposive sampling. The recorded interviews were transcribed and analyzed using a phenomenological method. To ensure reliability and validity in the data analysis process, grounded in Husserlian phenomenology and Giorgi's phenomenological method were employed. Results Seven key themes related to the perceptions of caring behavior emerged from the phenomenological analysis: (1) Caring as trying one's best to meet patients’ needs; (2) Caring as a central value of nursing practice; (3) Caring as compassion; (4) Caring as helping each other; (5) Caring as awareness of patients’ individual needs; (6) Caring as professionalism; and (7) Caring as support. Conclusion The findings of this study are expected to significantly improve nursing student application of caring behavior in the clinical setting. Increasing understanding and application of caring behavior in nursing students can have a positive impact on clinical practice. This study is useful as a guide for educators to help nursing students improve their caring practice in the clinical setting.